Knowledge and attitudes of mothers towards oxygen administration to their children at Entebbe regional referral hospital, Wakiso District. A cross-sectional study. - Alol, Monica; Nansereko, Hasifa; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Naggulu , Immaculate Posperia (Student's Journal of Health Research Africa, 2025)
Background Oxygen therapy has been an important aspect in clinical practice for more than 20 years. This study aimed to assess the knowledge and attitudes of mothers towards oxygen administration to their children at Entebbe Regional Referral Hospital, Wakiso district. Methods. A cross-sectional study design was employed, utilizing quantitative approach to data collection through a semi-structured questionnaire. The information was manually tallied, and scientific measures were used to analyze the recorded information. Thereafter, Microsoft Word and Excel programs were employed, followed by presentation in the form of frequency tables, graphs, and figures like pie charts and bar graphs. Results The majority of the participants were aged 20-29 years, 80% had attained Primary level education and 52% were either unemployed or were housewives, and 38% had between 2-3 children. 70% had no knowledge about Oxygen therapy for children with breathing problems, and 38% felt uncomfortable when their children were receiving oxygen therapy; 70% were concerned about risks when their children were administered oxygen therapy. Conclusion. The survey revealed that overall, all knowledge and attitudes of mothers towards oxygen administration were inadequate; however, the domains of attitudes towards oxygen administration need to be improved. Recommendations. MoH and partners should strive to increase the knowledge of mothers about the importance of oxygen therapy.